Goshajinkigan reduces bortezomib-induced mechanical allodynia in rats: Possible involvement of kappa opioid receptor - Hitomi Higuchi; Shota Yamamoto; Soichiro Ushio; Takehiro Kawashiri; Nobuaki Egashira (Elsevier, 2015)
In the present study, we investigated the effect of a Kampo medicine Goshajinkigan (GJG) on the bortezomib-induced mechanical allodynia in von Frey test in rats. The single administration of tramadol (10 mg/kg), GJG (1.0 g/kg) and its component processed Aconiti tuber (0.1 g/kg) significantly reversed the reduction in withdrawal threshold by bortezomib. These effects were abolished by the intrathecal injection of nor-binaltorphimine (10 μg/body), kappa opioid receptor antagonist. These findings suggest that kappa opioid receptor is involved in the effect of GJG on the bortezomib-induced mechanical allodynia.